SMOOTH MYOCYTES AND COLLAGENOUS FIBERS OF THE URINARY BLADDER OF RATS IN DIABETES MELLITUS - Nadiya Tokaruk (Journal of Education, Health and Sport, 2015)
Tokaruk Nadiya. Smooth myocytes and collagenous fibers of the urinary bladder of rats in diabetes mellitus. Journal of Education, Health and Sport. 2015;5(12):11-22. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34428